The Potential of Nyamplung Seed Oil Extract and Aloe Vera as Anti-Inflammatory Against Staphylococcus aureus Bacteria in Body Wash Preparations - Lestari, Suci Winda; Zulfa, Zulfa; Ariani, Sunniarti; Asriwanti, Nurul; Khadijah, St (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Skin problems caused by Staphylococcus aureus infection remain a challenge in healthcare and personal hygiene due to their ability to trigger inflammatory responses through the activation of pro-inflammatory cytokines. The extensive use of synthetic antibacterial agents such as triclosan in body wash products has contributed to bacterial resistance, highlighting the need for safer natural alternatives. Nyamplung seed oil contains bioactive compounds, including calophyllolide, inophyllum B, flavonoids, and triterpenoids, which exhibit antibacterial activity against Staphylococcus aureus. Aloe vera also contains aloin, emodin, saponins, and polysaccharides with antimicrobial and anti-inflammatory properties. This study aimed to evaluate the potential of nyamplung seed oil and aloe vera extracts as active ingredients in body wash formulations to inhibit Staphylococcus aureus growth and alleviate skin inflammation. A laboratory experimental design was employed, in which nyamplung seed oil was extracted using the Soxhlet method, while aloe vera was processed by blending and concentrated through heating. The formulated body wash showed a pH of 9.45, homogeneous liquid consistency, yellow color, and a characteristic aroma of nyamplung oil. Antibacterial testing revealed an inhibition zone diameter of 28 mm against Staphylococcus aureus, indicating strong antibacterial potential.